Assessing Professional Tour Guides’ Attitudes towards Cultural Heritage Based on Demographic Variables - Yalçınkaya, Tarık; Yaşlı, Azra (Fırat University, 2026)
Cultural heritage is valued for its ability to represent a society's past and foster a feeling of identity. Being a relatively recent topic of study, cultural heritage naturally lends itself to multidisciplinary research and tourism is one of these fields. Cultural heritage values that improve tourism experiences and provide answers to specific issues facing the industry are crucial for tourism-related activities. On the other hand, professional tour guides also play a key role in tourism. So, disclosing their perspectives on cultural heritage, their degree of expertise, and the actions that need to be done in this area will help to advance sustainable tourism. This study aims to assess the attitudes of professional tour guides towards cultural heritage. 366 valid questionnaires from professional tour guides working in Türkiye were collected during the study. The findings suggest that there were no statistically significant differences in the attitudes of professional tour guides on cultural heritage based on demographic variables such as gender, income, level of education, age, and years of experience. It is believed to contribute to the relevant literature.

Bir toplumun geçmişini temsil etme ve kimlik duygusunu besleme özelliğine sahip kültürel miras unsurları değer taşımaktadır. Nispeten yeni bir çalışma konusu olan kültürel miras, doğası gereği çok disiplinli araştırmalara uygundur ve turizm de bu alanlardan biri olarak ön plana çıkmaktadır. Turizm deneyimlerini iyileştiren ve sektörün karşı karşıya olduğu belirli sorunlara çözüm sunan kültürel miras değerleri, turizm faaliyetleri için önem arz etmektedir. Öte yandan, profesyonel turist rehberleri de turizmde önemli bir rol paydaş olarak kabul edilir. Bu nedenle, profesyonel turist rehberlerinin kültürel mirasa ilişkin bakış açılarını, uzmanlık derecelerini ve bu alanda atmaları gereken adımları araştırmak, sürdürülebilir turizmi ilerletmeye yardımcı olacaktır. Bu çalışma, profesyonel turist rehberlerinin kültürel mirasa yönelik tutumlarını değerlendirmeyi amaçlamaktadır. Çalışma sırasında Türkiye'de çalışan profesyonel tur rehberlerinden 366 geçerli anket toplanmıştır. Bulgular, cinsiyet, gelir, eğitim düzeyi, yaş ve deneyim yılı gibi demografik değişkenlere dayalı olarak profesyonel turist rehberlerinin kültürel mirasa yönelik tutumlarında istatistiksel olarak anlamlı bir fark olmadığını göstermektedir. Sonuçların ilgili literatüre katkıda bulunacağına inanılmaktadır.
Profesyonel Turist Rehberlerinin Kültürel Mirasa yönelik Tutumlarının Demografik Değişkenlere göre Belirlenmesi
Keywords: Cultural Heritage Tourism; Visitor and Audience Studies; Kültürel Miras Turizmi; Ziyaretçi ve İzleyici Çalışmaları